2015
DOI: 10.1007/s13760-015-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum level of IL-37 in patients with multiple sclerosis and neuromyelitis optica

Abstract: Multiple sclerosis (MS) is a common autoimmune disease of central nervous system in which neurodegenerative and inflammatory mechanisms cause alternate neurological impairments. Many inflammatory and anti-inflammatory cytokines were suggested as contributor in MS pathogenesis, and the balance between these opposing cytokines can regulate MS severity. IL-37, an anti-inflammatory cytokine, is the most recently identified member of IL-1 family, which acts as a natural inhibitor of innate immunity. However, the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
(30 reference statements)
3
23
0
Order By: Relevance
“…IL-37, a novel member of the IL-1 family, has been recognized as an important anti-inflammatory cytokine expressed by immune cells. Abnormal expression of IL-37 has been reported in various autoimmune diseases, including SLE, RA, IBD, GD and AS (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), as a potential negative factor influencing the development of these disorders. According to Ye et al (22), increased IL-37 expression was associated with SLE disease activity, and IL-37 levels were significantly higher in patients with renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-37, a novel member of the IL-1 family, has been recognized as an important anti-inflammatory cytokine expressed by immune cells. Abnormal expression of IL-37 has been reported in various autoimmune diseases, including SLE, RA, IBD, GD and AS (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), as a potential negative factor influencing the development of these disorders. According to Ye et al (22), increased IL-37 expression was associated with SLE disease activity, and IL-37 levels were significantly higher in patients with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of IL-37 has been observed in several inflammatory and autoimmune diseases, including rheumatoid arthritis (RA) (18)(19)(20)(21), systemic lupus erythematosus (SLE) (22,23), inflammatory bowel disease (IBD) (24,25), ankylosing spondylitis (AS) (26) and Graves' disease (GD) (27). However, the role of IL-37 in ITP has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of IL-37 has been reported in autoimmune diseases, such systemic lupus erythematosus (40), rheumatoid arthritis (41), inflammatory bowel disease (42), and psoriasis (43); however, its role in MS has not yet been documented. Only a recent paper demonstrated an increased serum level of IL-37 in patients with MS, which suggests that this cytokine is a part of a feedback loop to control the underlying inflammation in MS pathogenesis (44). IL-37 generally acts via an intracellular mechanism that translocates to the nucleus (22, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Farrokhi et al showed that IL37 serum levels were higher both in patients suffering from relapsing-remitting MS (RR-MS) and those with neuromyelitis optica (NMO) as compared to healthy controls. In addition, they noticed a positive correlation between the serum levels of IL37 and Expanded Disability Status Scale (EDSS) of patients [33]. These findings were subsequently confirmed in another independent study that demonstrated that serum levels of IL37 were higher in patients with MS and correlated with disease activity as well as with the levels of IL33 and soluble vascular endothelial growth factor (VEGF) receptor 2 [34].…”
Section: Introductionmentioning
confidence: 71%
“…In spite of these data of IL37 in autoimmune diseases, only a limited number of studies have evaluated the possible role of this cytokine in MS [33][34][35][36]. Farrokhi et al showed that IL37 serum levels were higher both in patients suffering from relapsing-remitting MS (RR-MS) and those with neuromyelitis optica (NMO) as compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%